Dysregulated IL-1β Secretion in Autoinflammatory Diseases: A Matter of Stress? - Carta, Sonia; Semino, Claudia; Sitia, Roberto; Rubartelli, Anna (Frontiers in Immunology, 2017)
Infectious and sterile inflammation are induced by activation of innate immune cells. Triggering of Toll-like receptors by Pathogen- or Damage-associated molecular pattern molecules (PAMPs or DAMPs) generates reactive oxygen species (ROS) that in turn induce production and activation of pro-inflammatory cytokines such as IL-1β. Recent evidence indicates that cell stress due to common events, like starvation, enhanced metabolic demand, cold or heat, not only potentiates inflammation but may also directly trigger it in the absence of PAMPs or DAMPs. Stress-mediated inflammation is also a common feature of many hereditary disorders, due to the proteotoxic effects of mutant proteins. We propose that harmful mutant proteins can induce dysregulated IL-1β production and inflammation through different pathways depending on the cell type involved. When expressed in professional inflammatory cells, stress induced by the mutant protein activates in a cell-autonomous way the onset of inflammation and mediates its aberrant development, resulting in the explosive responses that hallmark autoinflammatory diseases. When expressed in non-immune cells, the mutant protein may cause the release of transcellular stress signals that trigger and propagate inflammation.